Real and perceived minority influences in medieval society: introduction. Issue 3 (27th May 2019) - Berend, Nora
ABSTRACT: The introduction to this special issue first engages with the concept of 'minority' and its critics, arguing for a reasoned use of the notion. Then it discusses patterns of influence based on the papers: the ways in which minorities contributed to society, how majority societies borrowed from minorities, how minoritising discourses worked, how positive and negative perceptions were triggered, and what the function of such perceptions were.